Stakeholders’ impact on the environmental responsibility: Model design and testing - Smaliukienė, Rasa (Journal of Business Economics and Management, 2007)
The study is based on comparative theoretical research into the concepts of corporate social and environmental responsibilities. Multinational enterprises (MNEs) are responsive to the stakeholders’ needs. Therefore, environmental business management was integrated into model of corporate social responsibility. This demonstrates that social processes influencing corporate social responsibility are of equal importance for the development of environmental responsibility. Simultaneously, this theoretical integration leads to an understanding that corporate environmental responsibility may be also introduced into other theoretical models of social responsibility, which assess impacts of stakeholders and other social influences. The empirical research demonstrates that environmental expectations of stakeholders are different in economically different countries. In addition, the stakeholders differently see the functions of business in environmental issues. Qualitative content analysis disclosed what form of environmental responsibility is proper in countries of developed, developing and emerging economies. In developing economies, donations are demanded most of all; in emerging economies exposed to various transformations, there is a need for social investments; in developed economies full business co‐operation is preferred on environmental issues. Most important environmental outcomes of MNEs, as reflected in their annual statements, demonstrate business adaptation to different stakeholders’ expectations built in economically different countries. First Published Online: 14 Oct 2010